The Effectiveness of Teachers’ Feedback and Students' Self-Efficacy on Writing Competence of Eleventh - Grade Students at SMK N 3 Batam - Elvira, Yhosie; Ruminda, Ruminda; Juhana, Juhana (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines at how effectively eleventh-grade students at SMKN 3 Batam may improve their writing skills by incorporating teacher feedback and students' self-efficacy. Seventy students from two intact classes participated in a quantitative quasi-experimental design with pre-test and post-test control groups. While the control group received conventional instruction, the experimental group received self-efficacy treatments along with structured feedback. The integrated method successfully improves linguistic accuracy, confidence, and overall writing ability, according to the results, which show a statistically significant improvement in the experimental group.